Consensus on audiological assessments (III): Middle-Ear Analysis - Spanish Audiological Society, AEDA (Auditio, 2021)
[This is the third article of a series of three consensus protocols established by AEDA] Middle Ear Analysis Middle-ear analysis is an objective method of measuring the function of the auditory peripheral mechanism. In daily clinical practice, the tests that are fundamentally performed are: timpanometry, the study of the stapedial reflex, the threshold of the stapedial reflex, the study of reflex fatigue and the study of tubal function. Tympanometry is an objective test that, by increasing or decreasing the pressure in the external auditory canal, makes it possible to measure the changes in the flow of energy through the middle ear in the tympanic membrane. The acoustic reflex is an objective test in which after the arrival of strong sound stimuli to the ear, reflex contractions of the muscles of the middle ear are produced, fixing the eardrum-oscicular system and avoiding vibratory injuries in the sound transmission. The Spanish Audiological Society (AEDA) presents with this text a suggestion for the normalization of Impedance.